Clinical effects of irrigation with Saussurea lappa extract in the treatment of chronic periodontitis: A pilot randomized trial - Shilpa Trivedi; Jaya Dixit (Wolters Kluwer Medknow Publications, 2015)
Introduction: Periodontitis is a chronic inflammatory disease manifested as the destruction of tooth supporting tissues, which may progress to tooth loss. The chemical antimicrobial agents are often applied locally into the periodontal pocket as adjuncts to conventional mechanical periodontal therapy, but these have various adverse effects. Root extract of Saussurea lappa has shown anti-inflammatory and anti-bacterial properties. Hence, the present study was aimed to assess and compare the effect of root extract of S. lappa to chlorhexidine gluconate as subgingival irrigant as an adjunct to scaling and root planing (SRP). Materials and Methods: Thirty chronic periodontitis patients in the age group of 25-45 years were selected for the study. Five hundred and forty periodontal pockets were treated by three different procedures: Group1: Subjects treated by SRP only, Group 2: In addition to SRP, irrigation with S. lappa extract was done and Group 3: Chlorhexidine was used as irrigant along with SRP. Periodontal clinical recordings (modified sulcular bleeding index, probing pocket depth, clinical attachment level, and the presence of pus discharge) were done at 0, 7, 14, 28, and 42 days. Results: The periodontal parameters studied improved in all the three groups over the time period. In 4-5 mm pockets, S. lappa treated group showed significant improvement than chlorhexidine treated group. Furthermore, a dramatic decrease in periodontal pockets with pus discharge was seen in this group. Conclusion: Subgingival irrigation with S. lappa might be a promising adjunct to conventional treatment options in the management of periodontal infections.